Environmental controls on peak carbon uptake across four Kenyan dryland ecosystems - Odongo, Vincent O.; Leitner, Sonja; Räsänen, M.; Omondi, J.O.; Pellikka, P.; Vesala, T.; Heiskanen, J.; Rinne, J.; Dowling, T.P.F.; Korczynski, J.; Wooster, M.J.; Mauder, M.; et al. (International livestock research Institute, 2025)
Semi-arid and dry sub-humid landscapes dominate much of Kenya, yet their role in the regional carbon cycle is poorly quantified, particularly how peak ecosystem photosynthesis responds to variable wet-season rainfall. We synthesized eddy covariance observations from four contrasting sites: Kapiti, an open grassland rangeland; Choke, a wooded savanna; Maktau, a smallholder cropland; and Ausquest, a commercial cropland. All experience distinct wet and dry seasons but differ in rainfall, vegetation structure, and management. We focused on the wet season, when most annual carbon uptake occurs, to identify climatic and biophysical controls on maximum CO₂ uptake (NEEmax). Specifically, we assessed how rainfall and soil moisture regulate uptake, how temperature and vapor pressure deficit (VPD) constrain uptake under high light, and how land cover and management mediate water-carbon coupling. Comparing across this land-use gradient improves understanding of carbon-water exchange in East African drylands and their likely responses to future climate and land-use change.